Observations of the summer breakup of an Arctic sea ice cover. Issue 19 (9th October 2015) - Arntsen, Alexandra E.; Song, Arnold J.; Perovich, Donald K.; Richter‐Menge, Jacqueline A.
Abstract The Arctic sea ice cover evolves dramatically through the summer melt season. Floe size distribution (FSD) is a critical parameter used to examine this change as the ice cover transitions from large rectilinear plates in spring to an ensemble of discrete rounded floes by midsummer. The FSD at a given time impacts the dynamic and thermodynamic behavior of the ice cover. Focusing on the seasonal marginal ice zone in the Beaufort and Chukchi Seas from May to September 2014, we present qualitative and quantitative results derived from National Technical Means high‐resolution imagery and supported by ice mass balance buoy data. Results indicate that as melt accelerates, floe breaking pattern, and therefore FSD, is heavily influenced by the distribution of melt ponds. Discrete element model results using morphological conditions derived from analyzed satellite imagery confirmed that breaking occurs along ponds and perpendicular to applied stress.